UPAYA MENINGKATKAN HASIL BELAJAR KOGNITIF PESERTA DIDIK PADA MATERI ALAT OPTIK MELALUI PENERAPAN PROBLEM-BASED LEARNING BERBANTUAN THINKING MAP DAN BAHAN BACAAN DIGITAL - Fauzi, Toni Dwi; Fitria; Vari, Yonatan (Charm Sains: Jurnal Pendidikan Fisika, 2025)
The Problem-Based Learning (PBL) model provides opportunities for students to develop critical thinking and higher-order thinking skills in solving problems. However, in the pre-cycle stage, students’ cognitive learning outcomes on geometric optics material were still low. This classroom action research aimed to improve students’ cognitive learning outcomes through the implementation of PBL combined with Thinking Maps and digital reading materials on the topic of optical instruments. The subjects were 35 eleventh-grade students at a senior high school in Palangka Raya City. The study was conducted in two cycles consisting of planning, implementation, observation, and reflection stages. The results showed an increase in classical mastery from 71.42% with an average score of 74.74 in the first cycle to 80% with an average score of 77.82 in the second cycle, which met the success indicators as more than 75% of students achieved learning mastery and the class average exceeded the minimum mastery criterion. The implementation of PBL assisted by Thinking Maps and digital reading materials effectively helped students gain a deeper understanding of optical instrument concepts. This finding provides practical contributions for teachers in optimizing PBL strategies integrated with visual thinking tools and digital learning resources to improve physics learning outcomes.